Rare Clinical Course of Immunoglobulin G4-Related Inflammatory Abdominal Aortic Aneurysm with Multiple Rare Complications - Yuji Naito; Tsukasa Miyatake; Manami Iwasaki; Atsushi Okuyama; Akio Takada; Koji Chiba; Masahiko Obata; Junichi Oba (Case Reports in Vascular Medicine)
Immunoglobulin G4- (IgG4-) related inflammatory abdominal aortic aneurysm (AAA) has been recognized as a manifestation of IgG4-related disease (IgG4-RD). We experienced one patient with multiple consecutive manifestations before and after endovascular stent grafting for IgG4-related inflammatory AAA (IAAA). A 71-year-old man was diagnosed with IgG4-RD due to increased IgG4 serum concentration, typical findings of parotid gland biopsy, and periaortitis in another hospital 2 years and 7 months before visiting our hospital. He came to our hospital because of abdominal pain and IAAA. He developed paraplegia after hospitalization and underwent endovascular stent grafting for the IAAA. About one month after stent grafting, he developed perforation of the sigmoid colon due to enteritis. He also had myocardial infarction. Finally, he died of intestinal bleeding. Here, we describe this case with rare, multiple, consecutive manifestations of IgG4-RD, some of which might be caused by IgG4-related IAAA or side effects of treatments rather than by IgG4-RD itself. We report this case because the clinical course seemed rare for IgG4-RD or IgG4-related IAAA. For treating IgG4-RD with IgG4-related IAAA, we should consider factors causing the symptoms and carefully select the proper treatment.